Companies' growth in the EU: What is research and innovation policy's role? - Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2011)
One of the main objectives of the new European research and innovation policy agenda is to favour the positive demographics (creation and growth) of EU companies operating in new/knowledge-intensive industries, especially Small and Medium Enterprises (SMEs). These companies play an important role in shaping the dynamism of the economy's sectoral composition, favouring the transition towards more knowledge-intensive activities (smart growth) and in contributing to the overall economic growth objectives and more and better jobs. But which kind of companies should be helped by policy? And how? This paper presents a literature review on the economics of research, innovation and competitiveness, focusing on the evidence available regarding the determinants for new and existing company creation and growth and the role played by Research, Development (R&D) and innovation. Furthermore, based on this, it draws a number of policy implications to design future research and innovation support instruments targeting innovative company growth in Europe. The result of this work indicates that: a) EU needs support policies to foster R&D investment in some specific typology of innovative companies and only where there are market failures and clear high social returns; b) the establishment of any targeted support instruments should take into account an integrated set of criteria including: firms' age and size, the sectors where firms operate, the involved risks in and potential for their innovative and commercial activities, the country/techno-economic environment, and the degree of internationalisation; c) to be successful, no matter the new targeted policies and supporting instruments, they should be designed using policy experimentation and its results should be regularly measured and evaluated using appropriate indicators and analyses.
Keywords: O31; L25; R38; 330; Firm demographics and growth; Small and Medium Enterprises; economic dynamics; corporate research and innovation; EU competitiveness; EU policy.